PENGARUH BERBAGAI DOSIS PUPUK ORGANIK CAIR URIN SAPI TERHADAP PERTUMBUHAN SEMAI JABON MERAH (Anthocephalus macrophyllus (Roxb.) Havil) - Supriyanto, Supriyanto; Muslimin, Muslimin; Umar, Husain (Jurnal Warta Rimba, 2014)
Jabon Red (Anthocephalus macrophyllus Roxb.) Havil.) is a timber species that is currently intensively planted by people of Indonesia because it has a rapid growth and multi-function. The aim of this study was to determine the effect of various doses of liquid organic fertilizer of cow urine on the growth of Jabon Red seedlings (Anthocephalus macrophyllus Roxb) Havil). The experiment was conducted at the Green House and Forestry Science Laboratory, Forestry Faculty, Tadulako University, on March to May 2014. This study employed a completely randomized design (CRD), which consists of five levels of treatment, they are M0 = 0 ml / liter of water (control) M1 = 150 ml / liter of water, M2 = 250 ml / liter of water, the M3 = 350 ml / liter of water, M4 = 450 ml / liter of water. On these five treatments, they were replicated in each of four replications, so that, the total seedlings required were 20 samples. Observed variables are the increase of plant height, leaf number, diameter, fresh weight and dry weight of Jabon seedling. To find out the difference between treatments, then, it was tested Honestly Significant Difference (HSD). The results of this study addressed that dosing of liquid organic fertilizer of cow urine, having an extremely significant effects on seedling growth of Jabon Red (Anthocephalus macrophyllus Roxb) Havil. This was evidenced by the increase in plant height, leaf number, diameter, fresh weight and dry weight of Jabon seedling compared to jabon seedling without fertilizer. Dosing 150ml / l of water gives better Jabon seedling growth, of all treatments were tested with an average of 6.38 cm increase in plant height, number of leaves strands was 6.50, diameter of trunk was 1.65 mm, fresh weight of shoots was 5.56 grams and dry weight of shoots was 0.55 grams. Keywords: Red Jabon, Liquid Organic Fertilizer, Cow Urine, doses given